2003
DOI: 10.1046/j.1365-2141.2003.04655.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of haploidentical stem cell transplantation in the management of children with haematological disorders

Abstract: The broader application of stem cell transplantation (SCT) for paediatric diseases has been limited by a lack of human leucocyte antigen (HLA)-matched donors. Virtually all children, however have at least one haploidentical parent who could serve as a donor. Such a donor is immediately available and the considerable costs of additional HLA typing, registry and banking expenditures that are necessary to procure an unrelated donor, could be reduced. Recent technological advances appear to have overcome the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 112 publications
(150 reference statements)
1
21
0
Order By: Relevance
“…Delayed recovery of adaptive immunity results from the degree of HLA disparity, the low numbers of T cells infused in the graft, and the use of ATG, which may inhibit T-cell expansion. 12 Pediatric studies show that the median time to normal T and B cell numbers and proliferative responses was 7-8 months and our patients have similar reconstitution profiles. 8 Initial T-cell recovery is of oligoclonal memory T cells as a result of expansion of peripheral T cells from the graft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed recovery of adaptive immunity results from the degree of HLA disparity, the low numbers of T cells infused in the graft, and the use of ATG, which may inhibit T-cell expansion. 12 Pediatric studies show that the median time to normal T and B cell numbers and proliferative responses was 7-8 months and our patients have similar reconstitution profiles. 8 Initial T-cell recovery is of oligoclonal memory T cells as a result of expansion of peripheral T cells from the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally reported that the problems of engraftment have been overcome in haplo-identical PBSCT, all centers undertaking this procedure have occasional patients with a dysfunctional graft. [11][12][13] However, even though some failures may be explained by differences in immune suppression given pre-transplant and lower doses of CD34 þ cells infused, 14,15 there is no doubt that not all patients receiving mega doses of CD34 þ cells are guaranteed engraftment. 16 Our relatively high levels of graft dysfunction cannot be explained by either low numbers of CD34 þ cells infused nor insufficient pre-transplant immune suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, higher numbers of infectious deaths are reported in adults 44 than in children, probably reflecting an impaired thymic function in older patients. 45 In haplo-SCT with CD34 þ selected stem cells, infections with adenovirus (ADV), CMV and Aspergillus remained a significant cause of mortality in children within the first 6 months post transplant. Incidences of CMV reactivation between 14 and 29% have been reported, leading to lethal infections in 0-8%.…”
Section: Immune Reconstitution and Trmmentioning
confidence: 99%
“…[1][2][3][4] Nearly all patients have a haploidentical donor within the family and, in contrast, to an unrelated donor search, the haploidentical family donor is rapidly available. The role of natural killer (NK)-cell alloreactivity in haploidentical HSCT 5 to promote engraftment and graft-versus-leukemia (GvL) effects is increasingly recognized.…”
Section: Introductionmentioning
confidence: 99%